My Migraine Voice survey: disease impact on healthcare resource utilization, personal and working life in Finland - Marja-Liisa Sumelahti; Markku Sumanen; Merika S. Sumanen; Samuli Tuominen; Johanna Vikkula; Sanna M. Honkala; Stina Rosqvist; Minna A. Korolainen (The Journal of Headache and Pain, 2020)
Abstract Background A global My Migraine Voice survey was conducted in 31 countries among 11,266 adults who suffered from ≥4 monthly migraine days (MMD). The aim of this retrospective observational survey-based study was to analyse the country specific results in Finland in order to understand the impact of migraine based on disease severity. Methods The included participants (3%, n = 338/11,266) were stratified by mean MMDs into 4 ≤ MMD < 8 (n = 133), 8 ≤ MMD < 15 (n = 139) and MMD ≥ 15 (n = 66) subgroups. Comorbidities, migraine-related emotional burden and impact on daily living and work productivity and activity impairment (WPAI) were assessed. Subgroup analysis on healthcare resource utilization (HCRU) due to migraine was assessed by visits to healthcare practitioners (HCPs) during the past 6 months and by hospitalizations and emergency room (ER) visits during the past 12 months. The group difference was tested using the one-way ANOVA and for categorical variables using the Chi-squared test. The association between HCRU and MMD and number of comorbidities was assessed using negative binomial regression analysis. Results Mean age was 44 years, 93% were women and 67% (n = 227) were employed. Chronic migraine (CM, MMD ≥ 15) was reported in 19.5% of the respondents. The negative impact on daily functioning and emotional burden increased significantly by migraine frequency. Mean number of comorbidities was 2.4, and mean number of HCP visits during the previous 6 months was 5.9. Increase in migraine frequency and comorbidities was associated with higher HCRU. Eighty-eight percent of the respondents reported negative impact on working life and 52% experienced overall work productivity impairment. Over previous month, the mean number of missed working days for all respondents was 2.8 days of which 54% were paid sick leave days, and in CM up to 6.0 days and 30%, respectively. Both absenteeism and presenteeism were higher in the CM group. Conclusions The emotional and functional burden was high, and the societal burden increased by frequency and severity of migraine, as shown by higher HCRU and reduced work productivity. There is a need to improve quality of care in migraine and improve migraine management related issues in both healthcare and society in Finland.